2014
DOI: 10.1094/phyto-08-13-0227-r
|View full text |Cite
|
Sign up to set email alerts
|

Southern rice black-streaked dwarf virus Alters Insect Vectors' Host Orientation Preferences to Enhance Spread and Increase Rice ragged stunt virus Co-Infection

Abstract: In recent years, Southern rice black-streaked dwarf virus (SRBSDV), a tentative species in the genus Fijivirus (family Reoviridae), has spread rapidly and caused serious rice losses in eastern and southeastern Asia. With this virus spread, Rice ragged stunt virus (RRSV, genus Oryzavirus, family Reoviridae) became more common in southern China, usually in co-infection with the former. SRBSDV and RRSV are transmitted by two different species of planthoppers, white-backed planthopper (WBPH, Sogatella furcifera) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
68
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(74 citation statements)
references
References 26 publications
4
68
1
1
Order By: Relevance
“…For example, SRBSDV-infected plants are more attractive to nonviruliferous S. furcifera individuals but less so to the viruliferous ones, whereas healthy plants are more attractive to the viruliferous but less so to the nonviruliferous individuals (131). Furthermore, RRSV-carrying N. lugens individuals prefer SRBSDV-infected rice plants (62,104). Thus, rice reoviruses may alter the host's preference for vectors to enhance their transmission and for insects that vector another virus to result in coinfection with more than one virus (62,104).…”
Section: Ecological Impacts Of Virus-insect-plant Interactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, SRBSDV-infected plants are more attractive to nonviruliferous S. furcifera individuals but less so to the viruliferous ones, whereas healthy plants are more attractive to the viruliferous but less so to the nonviruliferous individuals (131). Furthermore, RRSV-carrying N. lugens individuals prefer SRBSDV-infected rice plants (62,104). Thus, rice reoviruses may alter the host's preference for vectors to enhance their transmission and for insects that vector another virus to result in coinfection with more than one virus (62,104).…”
Section: Ecological Impacts Of Virus-insect-plant Interactionsmentioning
confidence: 99%
“…Furthermore, RRSV-carrying N. lugens individuals prefer SRBSDV-infected rice plants (62,104). Thus, rice reoviruses may alter the host's preference for vectors to enhance their transmission and for insects that vector another virus to result in coinfection with more than one virus (62,104). Perhaps plant volatile organic emissions affect insects' preference for or attract them to virus-infected host plants, but this possibility has not been studied.…”
Section: Ecological Impacts Of Virus-insect-plant Interactionsmentioning
confidence: 99%
“…Luteovirid acquisition by aphids appears to alter host selection behavior to prefer uninfected plants while non-viruliferous aphids tend to prefer virus-infected plants, thereby promoting both virus acquisition and transmission [99,100]. Similar virus effects on host preferences of the vector were observed for reovirus-infected and virus-free planthoppers [101]. The nuclear inclusion a (NIa) protease protein of turnip mosaic potyvirus has been implicated in manipulating host plant physiology to attract aphid vectors and to promote their reproduction [102].…”
Section: Critical Steps In Virus–insect Interactions As Potential mentioning
confidence: 99%
“…It has been reported that host selection preference of insect vector may be altered by plant virus. For instance, viruliferous (Southern rice black-streaked dwarf virus) white-backed planthopper (WBPH) preferred healthy rice plants to infected plants, whereas virus-free WBPH preferred infected plants (Wang et al, 2014). The tripartite interactions of virus-vector-plant relationships are complex (Hogenhout et al, 2008).…”
mentioning
confidence: 99%